Prevalence of strongyloidiasis in the general population of the world: a systematic review and meta-analysis. (2nd January 2021) - Eslahi, Aida Vafae; Badri, Milad; Nahavandi, Kareem Hatam; Houshmand, Elham; Dalvand, Sahar; Riahi, Seyed Mohammad; Johkool, Morteza Ghanbari; Asadi, Negar; Hoseini Ahangari, Seyed Abedin; Taghipour, Ali; Zibaei, Mohammad; Khademvatan, Shahram
ABSTRACT: Strongyloides stercoralis is a neglected soil-transmitted helminth affects approximately 100-370 million people globally. The life cycle is unusual as only larvae can be found in stool specimens. Thecurrent review and meta-analysis represented the distribution of strongyloidiasis in general population of the world based on published papers. Five English databases (Science Direct, Scopus, PubMed, Web of Science, and Google Scholar(were explored for literature published before October 2019.Altogether 235 studies (862243 participants) was eligible. Regarding diagnostic method, the overall prevalence for studies performed microscopic, culture, immunological and molecular method was 1.47% (95% CI = 1.56%), 10.08% (95% CI = 8.99% - 11.16%), 23.88% (95% CI = 20.82% - 26.94%) and 9.3% (95% CI = 7.2% - 11.3%), respectively. Based on microscopic methods, the highest prevalence was related to the Western Pacific region [9.47% (95% CI = 8.55% - 10.39%)]. According to the culture method, Western Pacific region [21.36% (95% CI = 16.32% - 26.39%)] had the highest estimated pooled prevalence. In immunological studies, Eastern Mediterranean Region [40.72% (95% CI = 36.74% - 44.70%)] had the highest seroprevalence.Also in molecular surveys, the highest prevalence was related to the African region [19.72% (95% CI = 16.71% - 22.73%)]. The current study indicated that strongyloidiasis is still considered a health problem in many parts of the world. Thus a comprehensive control program and improvement of public health sectors are required.